Investigation of Relative Time Constant Influence of Inertial Part of Superheater on Quality of Steam Temperature Control Behind Boiler in Broad Band of Loading Variations - G. T. Kulakov; M. L. Harelyshava (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper is devoted to computational investigation of influence relative time constant of an object which changes in broad band on quality of steam temperature control behind a boiler with due account of value of regulating action in the system with PI- and PID- regulator. The simulation has been based on a single-loop automatic control system (ACS). It has been revealed that the less value of the relative time constant of an object leads to more integral control error in system with PID- regulator while operating external ACS perturbation. Decrease of numerical value of relative time constant of an object while operating external perturbation causes decrease of relative time concerning appearance of maximum dynamic control error from common relative control time.